(untitled) (Research, Society and Development, 2022)
Based on the environmental assumptions that permeate the role of researchers in enabling the use of waste in consumer goods, using sewage sludge in human consumption material has become the object of worldwide study because of the potential that it carries. Aiming to fulfill the sustainable role through the creation of mechanisms that favor the ecological coexistence between environment and human beings, the use of the calcined sewage sludge as a potentiator in the properties of the material is made possible through the construction materials, behavior. Coating mortars are currently evaluated by exposing, from the replacement of the cement by the calcined material, an effective applicability with respect to its resistance to deleterious agents. It is understood that to idealize unconventional materials with the use of residues that have high degradation power to the environment, ratifies the attempt to mitigate large and irreversible environmental impacts arising from improper and poorly planned disposal.